IgE glycans promote anti-IgE IgG autoantibodies that facilitate IgE serum clearance via Fc Receptors - Plattner, Kevin; Gharailoo, Zahra; Zinkhan, Simon; Engeroff, Paul; Bachmann, Martin F.; Vogel, Monique (Frontiers in Immunology, 2022)
Recent studies have shown that IgE glycosylation significantly impacts the ability of IgE to bind to its high-affinity receptor Fc𝜀RI and exert effector functions. We have recently demonstrated that immunizing mice with IgE in a complex with an allergen leads to a protective, glycan-dependent anti-IgE response. However, to what extent the glycans on IgE determine the induction of those antibodies and how they facilitate serum clearance is unclear. Therefore, we investigated the role of glycan-specific IgG anti-IgE autoantibodies in regulating serum IgE levels and preventing systemic anaphylaxis by passive immunization. For this purpose, mice were immunized using glycosylated or deglycosylated IgE-allergen-immune complexes (ICs) to induce IgG anti-IgE antibodies. The IgG anti-IgE antibodies were purified and used for passive immunization. Glycosylated IgE-ICs induced a significantly higher IgG anti-IgE response and more IgG-secreting plasma cells than deglycosylated IgE-ICs. Passive immunization of IgE-sensitized mice with purified IgG anti-IgE increased the clearance of IgE and prevented systemic anaphylaxis upon allergen challenge. IgG anti-IgE purified from the serum of mice immunized with deglycosylated IgE-ICs, led to a significantly reduced elimination and protection, confirming that the IgE glycans themselves are the primary drivers of the protectivity induced by the IgE-immune complexes. Therefore, IgE glycosylation is essential for a robust IgG anti-IgE response and might be an important regulator of serum IgE levels.